Bio-milling technique for the size reduction of chemically synthesized BiMnO3 nanoplates - Mazumder, Baishakhi; Uddin, Imran; Khan, Shadab; Ravi, Venkat; Selvraj, Kaliaperumal; Poddar, Pankaj; Ahmad, Absar (Journal of Materials Chemistry, 2007)
Wet- chemical techniques for the synthesis of complex oxide materials have advanced significantly; however, achieving finely dispersed nanoparticles with sizes less than 10 nm still remains challenging, especially for the perovskite family of compounds. On the other hand, a fungusmediated synthesis technique has recently shown potential to synthesize perovskites such as BaTiO3 with sizes as small as 5 nm. Here we report, for the first time, the use of fungal biomass, at room temperature, to break down chemically synthesized BiMnO3 nanoplates ( size similar to 150 - 200 nm) into very small particles (, 10 nm) while maintaining their crystalline structure and the phase purity. This novel technique that we have named as `` bio- milling'' holds immense potential for synergically utilizing both chemical and biological synthesis techniques to synthesize complex oxide nanoparticles with particle sizes less than 10 nm with the proper crystalline phase.

Field emission studies of silver nanoparticles synthesized by electron cyclotron resonance plasma - Purohit, Vishwas; Mazumder, Baishakhi; Bhise, Ashok B.; Poddar, Pankaj; Joag, Dilip S.; Bhoraskar, S. V. (Applied Surface Science, 2011)
Field emission has been studied for silver nanoparticles (25-200 nm), deposited within a cylindrical silver target in an electron cyclotron resonance (ECR) plasma. Particle size distribution was controlled by optimum biasing voltages between the chamber and the target. Presence of non-oxidized silver was confirmed from the X-Ray diffraction analysis; however, thin protective layer of oxide was identified from the selective area electron diffraction pattern obtained with transmission electron microscopy. The silver nanoparticles were seen to exhibit hilly pointed like structures when viewed under the atomic force microscopy (AFM). The emissive properties of these particles were investigated by field emission microscopy. It is found that this technique of deposition is ideal for formation of nanoparticles films on different substrate geometries with size controllability as well as its application to emission devices. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Cold plasma; field emission; Nanoparticles; thin film